Interaction of ultra-short laser pulses with metal surfaces: Impulsive jelliun-Volkov approximation versus the solution of the time-dependent Schrödinger equation - Faraggi, Marisa Noemi (2007)
Electron emission coming from the valence band of metal surfaces due to grazing incidence of  high frequency ultrashort laser pulses is studied. We introduce a distorted-wave method, named impulsive jellium-Volkov (IJV) approximation, in which the surface is represented by the jellium model while the interaction with the laser field is described by means of the Volkov phase. With the purpose of examining the proposed approach, we compare IJV results with values derived from the numerical solution of the corresponding time-dependent Schrödinger equation (TDSE). For Al(111) surfaces, double and single differential probability spectra are calculated considering different duration of the laser pulse. Very good agreement between IJV and TDSE results was found. The total probability dependence on the intensity and carrier-envelope phase of the pulse is also investigated.